2008
DOI: 10.1590/s1806-83242008000400008
|View full text |Cite
|
Sign up to set email alerts
|

Smoking enhances bone loss in anterior teeth in a Brazilian population: a retrospective cross-sectional study

Abstract: The aim of the present study was to radiographically evaluate the effect of smoking on bone loss resulting from chronic periodontitis. Periapical radiographs were analyzed of 80 patients with chronic periodontitis (40 current or former smokers and 40 never-smokers) that attended a private periodontal practice. The smokers or former-smokers with a minimum consumption of 10 cigarettes/day for a period of over 10 years were selected. Interproximal radiographic bone loss was considered as the distance between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 28 publications
1
14
0
2
Order By: Relevance
“…Susin et al 6 evaluated a representative sample of the Porto Alegre population (Rio Grande do Sul State, Brazil) and observed that smokers with moderate and strong dependence had 2.0 and 3.6 more risk, respectively, of having clinical attachment loss ≥ 5 mm than subjects who did not smoke. In another investigation, Lima et al 23 concluded that smoking enhances bone loss resulting from periodontitis.…”
Section: Smoking and Periodontal Tissues Epidemiological Studiesmentioning
confidence: 96%
“…Susin et al 6 evaluated a representative sample of the Porto Alegre population (Rio Grande do Sul State, Brazil) and observed that smokers with moderate and strong dependence had 2.0 and 3.6 more risk, respectively, of having clinical attachment loss ≥ 5 mm than subjects who did not smoke. In another investigation, Lima et al 23 concluded that smoking enhances bone loss resulting from periodontitis.…”
Section: Smoking and Periodontal Tissues Epidemiological Studiesmentioning
confidence: 96%
“…A nicotina tem sido associada a várias alterações celulares que podem contribuir para o início e posterior progressão da doença periodontal e, de acordo com Lima et al, 10 o desequilíbrio da concentração de nicotina pode levar alterações na resposta inflamatória. Baixa concentração de nicotina pode estimular a quimiotaxia dos neutrófilos, no entanto, altas concentrações podem prejudicar a fagocitose.…”
Section: Revisão De Literaturaunclassified
“…Essas alterações devem-se aos efeitos da nicotina no tecido periodontal, que dificulta a chegada das células inflamatórias no tecido e no sulco gengival, comprometendo o sistema de defesa local. 10 Para Bergstrom e Preber, 13 o desenvolvimento do processo inflamatório em fumantes é retardado, quando comparados ao desenvolvimento em não fumantes. Entretanto, Bastiaan et al 14 18 estudaram o número médio de sítios por pessoa, no qual houve piora em relação à profundidade de sondagem e perda de inserção ao longo de 10 anos, sendo que os tabagistas tiveram piora de 1,5 mm de profundidade de sondagem em comparação com os não fumantes que apresentaram 1,4 mm, sem diferença significativa.…”
unclassified
“…1,2 Several studies all around the world have pointed out a strong association between tobacco use/smoking habit and periodontal disease, evidenced by greater clinical attachment loss, gingival recession, and tooth loss, 3,4,5 as well as by reduced bone height and density. 6,7,8 The harmful effects of smoking on periodontal tissues are caused by cytotoxic and vasoactive substances present in tobacco, including nicotine, carbon monoxide, and reactive oxygen species. These substances cause oxidative stress and alter immunoinflammatory responses, reducing the functional activity of leukocytes, macrophages, lymphocytes, and other immune cells, and impairing wound healing and microbial identification.…”
Section: Introductionmentioning
confidence: 99%